2002
DOI: 10.1212/wnl.58.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose ACTH therapy for West syndrome

Abstract: Low-dose synthetic ACTH therapy is as effective for the treatment of WS as the higher doses used in previous studies. The dosage of synthetic ACTH used in the treatment of WS can be decreased as much as possible to avoid serious adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 27 publications
2
49
0
1
Order By: Relevance
“…This agrees with the results of a Japanese multi-institutional study of 138 patients with West syndrome. 2 This also showed that the severity of adverse effects correlated with the ACTH dosage, similar to our finding. Some studies, including this, showed death associated with higher dosages of ACTH.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This agrees with the results of a Japanese multi-institutional study of 138 patients with West syndrome. 2 This also showed that the severity of adverse effects correlated with the ACTH dosage, similar to our finding. Some studies, including this, showed death associated with higher dosages of ACTH.…”
Section: Discussionsupporting
confidence: 90%
“…*There were significant differences statistically between the cryptogenic group and the symptomatic group (P ϭ .0131), by2 test. 488 Hamano et al The Journal of Pediatrics • April 2006…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The CRH test was started between 08:00 and 09:00 a.m. on the third day or later after the last ACTH-Z injection (at the same time as "post-ACTH"). After CRH injection, blood samples were collected serially at 0, (15), 30, 60, 90, and 120 minutes for measurements of serum cortisol and plasma ACTH levels . In the CRH test, a serum cortisol increase to 20 µg/dL or higher is the criterion of normal HPA axis function [21][22][23].…”
Section: Evaluation Of the Hpa Axis Function (2): Corticotrophin-relementioning
confidence: 99%
“…Nonetheless, contrary to its proposed benefits, some adverse effects occurred during or after ACTH therapy. Hence, the dose of ACTH-Z was gradually reduced from 0.025 to 0.005-0.0125 mg/kg/dose once daily for 2 weeks and tapered in a phased manner [5][6][7][8][9][10][11][12][13][14][15]. Although the dose reduction minimized the adverse effects considerably, precaution is still needed for those adverse effects.…”
Section: Introductionmentioning
confidence: 99%